Synthesis, characterisation and optical studies of CdO-NiO NCs for comparative dye degradation study between two hazardous dyes Congo red and Rose Bengal - Rakesh Kumar Mandal; Abu Sayed Mondal; Sabyasachi Ghosh; Abhik Halder; Tapas Pal Majumder (Results in Chemistry, 2023)
In this study, CdO-NiO nano composites (NCs), CdO NPs, NiO NPs were synthesized by the help of chemical co precipitation method and investigated by XRD, SEM, UV–vis, PL and FTIR. Face centered cubic structure having Fm3m space group were observed by the help of XRD for both metal oxides CdO and NiO, their corresponding crystallite size obtained from WH plot are 73 nm and 16 nm presents in CdO-NiO NCs. Similarly we have observed FCC cubic structure for CdO and NiO which are synthesized separately. EDX reveals the elements present with their atomic percentage. Band gap for the NCs was calculated using tauc plot which is around 2.89 eV, 2.74 eV and 4 eV for CdO-NiO NCs, CdO NPs and NiO NPs respectively confirming their semi conducting nature. The presence of bonds Cd-O and Ni-O were confirmed using FTIR. An enhanced comparative photo catalytic activity in the presence of UV light for 140 min was also done for the two hazardous dyes Congo red with 90.18 % degradation [K = 0.0155 min−1, T50 = 45 min] and Rose bengal with 83.53 % degradation [K = 0.0126 min−1, T50 = 55 min] for CdO-NiO NCs. By similar observation for separately synthesized CdO NPs and NiO NPs, the corresponding values obtained are Congo red with 88.86 % degradation [K = 0.0165 min−1, T50 = 42 min], Rose bengal with 79.71 % degradation [K = 0.0117 min−1, T50 = 59.23 min] and Congo red with 87.81 % degradation [K = 0.0164 min−1, T50 = 42.25 min], Rose bengal with 82.68 % degradation [K = 0.0131 min−1, T50 = 52.90 min] respectively.